The Role of Diagnostic Assessment in the Preparation of Learning Strategies that Focus on the Needs of Students - Aco Karumpa K; M Agus A (STAI Hubbulwathan Duri, 2025)
This study aims to explore the role of diagnostic assessment in the preparation of learning strategies that focus on the needs of students. Diagnostic assessments are used to identify learners' strengths and weaknesses before the learning process begins, so educators can design more responsive and adaptive learning. This study uses a qualitative method with a case study approach that involves observation, interviews, and analysis of teaching modules that integrate the results of diagnostic assessments. The results showed that diagnostic assessment had a positive impact on learning effectiveness. Educators who use diagnostic assessments consistently can design learning that is more in line with the individual needs of students, both in terms of cognitive, social, and emotional abilities. In addition, feedback provided based on the results of the assessment can increase student motivation and engagement. Nonetheless, the study also found challenges in the implementation of diagnostic assessments, especially related to time constraints, educator skills, and the need for more intensive training. This study concludes that diagnostic assessment is an integral component in designing effective and inclusive learning strategies. For this reason, it is important for schools to provide support in the form of adequate training and resources so that diagnostic assessments can be applied optimally in daily learning.